Toads and Informers: How the British Treated their Collaborators during the Cyprus Emergency, 1955–9. Issue 1 (1st January 2017) - French, David
ABSTRACT: During the Cyprus Emergency the British administration made considerable use of both Cypriot and Turkish collaborators as policemen and civil servants. Most were able to sink back into the safety of their own ethnic community after the Emergency, but some had become pariahs and had to look to the departing British for succour. They were the small group of Greek Cypriots who actively collaborated with the British against EOKA (National Organization of Cypriot Fighters), and the even smaller group of Turkish Cypriots who worked with them against the Turkish underground organisation, TMT. This article uses newly released archival materials to explore the history of these collaborators, asking questions about their recruitment, their actions, and the risks and dangers they faced. Evidence emerges as to how the British rewarded and subsequently treated these collaborators, how those who applied for asylum fared, and what happened to them once they arrived in Britain.